Criteria-based comparison of Systems Engineering and agile methods - Humpert, Lynn; Mundt, Enrik; Bretz, Lukas; Bernz, Vanessa; Anacker, Harald; Dumitrescu, Roman (8th International Conference on Information Systems Engineering)

Mechanisches Verhalten: Charakterisierung von Klebstoffen - Tews, Karina; Teutenberg, Dominik; Meschut, Gerson (DECHEMA Workshop für Klebstoffanwender: Simulation von Klebverbindungen)

Improving Process Mining Maturity – From Intentions to Actions - Brock, Jonathan; Brennig, Katharina; Löhr, Bernd; Bartelheimer, Christian; von Enzberg, Sebastian; Dumitrescu, Roman (Business & Information Systems Engineering)
Abstract Process mining is advancing as a powerful tool for revealing valuable insights about process dynamics. Nevertheless, the imperative to employ process mining to enhance process transparency is a prevailing concern for organizations. Despite the widespread desire to integrate process mining as a pivotal catalyst for fostering a more agile and flexible Business Process Management (BPM) environment, many organizations face challenges in achieving widespread implementation and adoption due to deficiencies in various dimensions of process mining readiness. The current Information Systems (IS) knowledge base lacks a comprehensive framework to aid organizations in augmenting their process mining readiness and bridging this intention-action gap. The paper presents a Process Mining Maturity Model (P3M), refined through multiple iterations, which outlines five factors and 23 elements that organizations must address to increase their process mining readiness. The maturity model advances the understanding of how to close the intention-action gap of process mining initiatives in multiple dimensions. Furthermore, insights from a comprehensive analysis of data gathered in eleven qualitative interviews are drawn, elucidating 30 possible actions that organizations can implement to establish a more responsive and dynamic BPM environment by means of process mining.

Characterization of Interfacial Corrosion Behavior of Hybrid Laminate EN AW-6082 ∪ CFRP - Delp, Alexander; Wu, Shuang; Freund, Jonathan; Scholz, Ronja; Löbbecke, Miriam; Tröster, Thomas; Haubrich, Jan; Walther, Frank (Materials)
The corrosion behavior of a hybrid laminate consisting of laser-structured aluminum EN AW-6082 ∪ carbon fiber-reinforced polymer was investigated. Specimens were corroded in aqueous NaCl electrolyte (0.1 mol/L) over a period of up to 31 days and characterized continuously by means of scanning electron and light microscopy, supplemented by energy dispersive X-ray spectroscopy. Comparative linear sweep voltammetry was employed on the first and seventh day of the corrosion experiment. The influence of different laser morphologies and production process parameters on corrosion behavior was compared. The corrosion reaction mainly arises from the aluminum component and shows distinct differences in long-term corrosion morphology between pure EN AW-6082 and the hybrid laminate. Compared to short-term investigations, a strong influence of galvanic corrosion on the interface is assumed. No distinct influences of different laser structuring and process parameters on the corrosion behavior were detected. Weight measurements suggest a continuous loss of mass attributed to the detachment of corrosion products.

Use Cases of Generative AI In Factory Planning: Potential and Challenges - Disselkamp, Jan-Philipp; Kürpick, Christian; Schütte, Ben; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Towards business use cases of process mining in product development and manufacturing: Deriving and classifying 18 application scenarios in industry - Brock, Jonathan; Enzberg, Sebastian von; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Digital Factory Twin: A Practioner-Driven Approach for Integrated Planning of the Enterprise Architecture - Lick, Jonas; Disselkamp, Jan-Philipp; Kattenstroth, Fiona; Trienens, Malte; Rasor, Rik; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Challenges in the implementation of simulation models for the digital factory twin - a systematic literature review - Kattenstroth, Fiona; Disselkamp, Jan-Philipp; Lick, Jonas; Dumitrescu, Roman (Procedia CIRP)

Product and production design - Rethinking views on flexibility - Beibl, Julia; Disselkamp, Jan-Philipp; Dumitrescu, Roman; Krause, Dieter (Procedia CIRP)

Venture Clienting in Corporate Practice: What type of Established Companies are Using the Venture Client Model? - Haarmann, Lennard; Jobelius, Johannes J.; Machon, Fabian; Rabe, Martin; Kühn, Arno; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Start-ups have become a pillar of EC' open innovation initiatives. With the aim of accessing start-up innovation, established companies (EC) use various corporate venturing modes. However, as established corporate venturing modes (e.g. corporate venture capital or accelerators) do not provide direct access to start-up innovation, the venture client model (VCLM) is receiving increasing attention in corporate practice. In the VCLM, ECs become paying customers of start-ups without taking equity - they become venture clients. In joint pilot projects, they apply start-up solutions to their products, processes or business models in order to solve relevant business problems and create strategic impact for increased competitiveness. The literature lists different EC using the VCLM such as BMW, Bosch, Continental, Daimler, Siemens, or ZF. This suggests that the VCLM is only used in EC with tens of thousands of employees, from Germany and in technology-intensive sectors such as automotive, mechanical engineering or telecommunications. On the other hand, GIMMY describes the suitability of the VCLM for any EC. However, in order to develop practical solutions to the challenges of the VCLM (e.g. slow purchasing, legal and IT processes or lack of acceptance of start-ups as collaboration partners), it is necessary to know the users (type of EC) of these solutions. Therefore, the aim of this paper is to characterize the EC using the VCLM with respect to industry, size and regionality.

Engineering Genetics - Towards the Double Helix Model for Integrative Product and Production Design - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Lick, Jonas; Ptock, Lukas; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Model-Based Handling of Variability in Offer Management in Mechanical and Plant Engineering - Wilke, Daria; Bremer, Christian; Disselkamp, Jan-Philipp; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Guiding The Transformation To A Digital Factory Twin: Towards An Enterprise-Architecture-Management-based Approach With The Help Of A Capability Map - Lick, Jonas; Weller, Julian; Brock, Jonathan; Pathak, Shantanu; Disselkamp, Jan-Philipp; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Spearhead Data-Driven Model-Based Systems Engineering: Interview Study on Definition, Preconditions, Challenges, Potentials, and Use Cases - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of NordDesign 2024)

A Maturity Model for Data-Driven Model-Based Systems Engineering for Producing Companies - Tissen, Denis; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 26th International DSM Conference (DSM 2024), Stuttgart, Germany)

Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of NordDesign 2024)

The Venture Client Model and Its Challenges for Established Companies - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Kuhn, Arno; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Data from start to finish: A System Life Cycle Data Map - Tissen, Denis; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Toward Intelligent Generation of System Architectures - Von Heissen, Oliver; Hanke, Fabian; Mpidi Bita, Isaac; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Reference Architecture for the Integration of Prescriptive Analytics Use Cases in Smart Factories - Weller, Julian; Migenda, Nico; Naik, Yash; Heuwinkel, Tim; Kühn, Arno; Kohlhase, Martin; Schenck, Wolfram; Dumitrescu, Roman (Mathematics)
Prescriptive analytics plays an important role in decision making in smart factories by utilizing the available data to gain actionable insights. The planning, integration and development of such use cases still poses manifold challenges. Use cases are still being implemented as standalone versions; the existing IT-infrastructure is not fit for integrative bidirectional decision communication, and implementations only reach low technical readiness levels. We propose a reference architecture for the integration of prescriptive analytics use cases in smart factories. The method for the empirically grounded development of reference architectures by Galster and Avgeriou serves as a blueprint. Through the development and validation of a specific IoT-Factory use case, we demonstrate the efficacy of the proposed reference architecture. We expand the given reference architecture for one use case to the integration of a smart factory and its application to multiple use cases. Moreover, we identify the interdependency among multiple use cases within dynamic environments. Our prescriptive reference architecture provides a structured way to improve operational efficiency and optimize resource allocation.